(untitled) (Quinto Sol, 2018)
Emotions had long been marginalized from the historical enterprise. However, since the beginning of the 21st century, emotion not only turned into an analytic category and an autonomous object of research, but also contributed to shape a flourishing and rapidly expanding research domain. On the one hand, this paper outlines the process of shaping of the field of history of emotions which was prompted by a transdisciplinary perspective and a theoretical and methodological dialogue with the humanities and the social sciences, as well as, with the biomedical sciences and the neurosciences. And, on the other, it introduces current debates and sketches some of the future directions the field might take.